Computation-guided design of high-performance flexible thermoelectric modules for sunlight-to-electricity conversion. Issue 10 (1st September 2020) - Xu, Shengduo; Hong, Min; Shi, Xiaolei; Li, Meng; Sun, Qiang; Chen, Qixiang; Dargusch, Matthew; Zou, Jin; Chen, Zhi-Gang
Abstract : A computation-guided design of a flexible thermoelectric module achieves a high output power density of 3 μW cm −2 by sunlight-to-electricity conversion. Abstract : Due to the outstanding mechanical endurance and easy scale-up fabrication, printed poly(3, 4-ethylenedioxithiophene):poly(styrenesulfonate) (PEDOT:PSS) films are a promising thermoelectric material. However, their low thermoelectric performance, unreasonable device design and insufficient temperature gradient have significantly hindered the development of flexible PEDOT:PSS-based thermoelectric devices for their practical applications. To overcome these challenges, here we propose a novel method combining ethylene glycol pre-treatment and H2 SO4 post-treatment plus tetrakis(dimethylamino)ethylene post-treatment in sequence to engineer printed flexible PEDOT:PSS films. The ethylene glycol pre-treatment strengthens the selective removal of excess non-ionized PSS to create a clear path for the further H2 SO4 post-treatment, and in turn induces a structural conformation transition of the conjugated carbon chains in PEDOT:PSS films. The final tetrakis(dimethylamino)ethylene post-treatment induces a high power factor of 224 μW m −1 K −2 at room temperature by tuning the oxidation level of the fabricated PEDOT:PSS films. More importantly, we employ thermodynamic numerical analysis to computationally design and assemble a flexible module using the optimized PEDOT:PSS films. Such a module yields a record-high power output density of 3 μW cm −2 at a temperature gradient of 44.5 K induced by harvesting sunlight, and has no notable performance change after mechanical (1000 bending cycles), air stability (30-day air exposure) and thermal stability (20 heating and cooling cycles) tests. This study indicates that our computation-guided module can be widely applied to supply power for micro-watt electronics by virtue of the high-efficiency sunlight-to-electricity conversion.